Analisis Pemasaran Bunga Potong Krisan di Kelurahan Kakaskasen II Kecamatan Tomohon Utara Kota Tomohon (Marketing Margin Analysis Cut Flower Chrysanthemum of Kakasen II village in North Tomohon Subdistrict Tomohon Utara Regency) - Natalita Rumengan; Ribka M Kumaat; Caroline B.D. Pakasi (COCOS, 2016)
ABSTRACNatalitaRumengan.Marketing Margin Analysis Cut Flower Chrysanthemum Village Kakaskasen II in North Tomohon sub district Tomohon.Under the guidance of Ir.Ribka M. Kumaat, MS as chairman and Dr. Caroline B. D. Pakasi, SP., MSi as a member.The goal in this research, analyze marketing margins cut chrysanthemum flowers in the village Kakaskasen Two North Tomohon sub district Tomohon.The study lasted six months, from the preparation to the preparation of reports that in April 2016 to October 2016. The implementation of the research is in the Village Kakaskasen two North Tomohon sub district Tomohon. The data used in this research is the primary data is by asking based questionnaire to farmers and sellers of chrysanthemums in the village Kakaskasen II North Tomohon sub district City secondary Tomohon.Data obtained from the department of Agriculture and Village Office Tomohon Kakaskasen two. The sampling method was done by snowball sampling. Census were used in this research that the population of farmers growing cut flower chrysanthemum and subsequently traced to the owner florist chrysanthemum cut flowers in the village Kakaskasen II, up to the consumer level. The results showed, that the marketing margin obtained is 53.33%. The costs incurred by retailers that Rp.823,78 by stalk or 10,98%. While the profit margin obtained Rp.3.176,22 by stalk.